Investigating of fear of COVID-19 after pregnancy and association with breastfeeding (Journal of Ideas in Health, 2021)
Background: COVID-19 pandemic has certainly become the most important global problem. Deficient information may increase the fear of COVID-19, affect pregnant women's psychology, and even affect breastfeeding during the postpartum period. This study aimed to assess the fear of the COVID-19 pandemic after pregnancy and its association with breastfeeding.Methods: A cross-sectional study designed to survey all pregnant women who gave birth at ≥36 weeks between March 10 and June 10, 2020, at the Private Nisa Hospital, Istanbul, Turkey. Participants respond to questions related to sociodemographic, genealogical, pregnancy, birth information, postpartum baby care, and breastfeeding status, in addition to the 7-item Fear of COVID-19 Scale (fcv-19s) via phone. Descriptive, bivariate, and linear regression analysis was performed to predict fcv-19s. SPSS version 22.0 was used to analyze the data.Results: A total of 906 (response rate 78.8%) respondents with a mean age of 29.59 (±4.74years) were included in the study. Most of them were highly educated (75.2%), housewives(86.1%), and living in nuclear families (96.1%). The majority of women (92.9%) gave birth at 38 weeks via cesarean section (71.7%) and breastfeeding (94.2%). Although the mean score of (fcv-19s) was high in non-breastfeeding mothers, no significant correlation was seen in bivariate analysis. In the linear regression analysis, the highly educated, good income status, having at least once follow-up a month, having a history of psychiatric disease, cesarean section delivery, competence in baby care, breastfeeding, and milk adequacy significantly predicted the (fcv-19s) (R = 0.67, R2 = 0.46, F = 42.10, p < 0.001).Conclusions: During pandemics, including COVID-19, the psychological state of society is negatively affected, and therefore special attention must be given to the most affected groups, especially pregnant and postpartum women.
Keywords: SARS-CoV-2, Pandemics, Breastfeeding, Pregnancy, Fear of COVID-19, Istanbul, Turkey